Loss of YABBY2-Like Gene Expression May Underlie the Evolution of the Laminar Style in Canna and Contribute to Floral Morphological Diversity in the Zingiberales - Morioka, Kelsie; Yockteng, Roxana; Almeida, Ana M. R.; Specht, Chelsea D. (Frontiers in Plant Science, 2015)
The Zingiberales is an order of tropical monocots that exhibits diverse floral morphologies. The evolution of petaloid, laminar stamens, staminodes, and styles contributes to this diversity. The laminar style is a derived trait in the family Cannaceae and plays an important role in pollination as its surface is used for secondary pollen presentation. Previous work in the Zingiberales has implicated YABBY2-like genes, which function in promoting laminar outgrowth, in the evolution of stamen morphology. Here, we investigate the evolution and expression of Zingiberales YABBY2-like genes in order to understand the evolution of the laminar style in Canna. Phylogenetic analyses show that multiple duplication events have occurred in this gene lineage prior to the diversification of the Zingiberales. Reverse transcription-PCR in Canna, Costus, and Musa reveals differential expression across floral organs, taxa, and gene copies, and a role for YABBY2-like genes in the evolution of the laminar style is proposed. Selection tests indicate that almost all sites in conserved domains are under purifying selection, consistent with their functional relevance, and a motif unique to monocot YABBY2-like genes is identified. These results contribute to our understanding of the molecular mechanisms underlying the evolution of floral morphologies.